The paradox of stillness art, object, and performance - Cirauqui, Manuel ca. 20./21.Jh; Collingwood, Jadine 1985-; Folkerts, Hendrik 1984-; Lavigne, Emma 1968-; Wood, Catherine 1973- (Walker Art Center, 2020)
"Presenting works from the early 20th century to today, The Paradox of Stillness: Art, Object, and Performance examines the notion of stillness as both a performative and visual gesture, featuring practitioners who have constructed static or near-static experiments that hover somewhere between action and representation as they are experienced in the gallery space. The exhibition investigates performance from the perspective of the object rather than the body, examining how performance has reinterpreted traditional artistic media. Stillness and permanence are qualities typically seen as inherent to painting and sculpture-consider the frozen gestures of a historical tableau or the unyielding solidity of a bronze figure. The Paradox of Stillness, however, expands the artwork's quality of stillness to accommodate uncertain temporalities and physical states, investigating works that merge objects with human bodies suspended in motion. Featuring artists whose works include performative elements but also embrace acts, objects, and gestures that refer more to the inert qualities of painting or sculpture than to true staged action, The Paradox of Stillness rethinks the history of performance through its aesthetic investigations into the interplay of the fixed image and the live body."
Titel vom Cover, Titelzusatz vom Buchrücken; im Inneren erstreckt sich die Angabe des Titel und des Titelzusatzes auf mehrere Seiten
Impressum: Published on the occasion of the exhibition "The Paradox of Stillness : Art, Object, and Performance", curated by Vincenzo de Bellis and organized by the Walker Art Center, Minneapolis. - Walker Art Center, Minneapolis, April 18-July 26, 2020
Keywords: Geschichte 1900-2020; Performance -- Künste; Kunst; Stillstand -- Motiv; Ruhe -- Motiv; Art, Modern / 20th century / Exhibitions; Art, Modern / 21st century / Exhibitions; Action in art / Exhibitions; Action in art; Art, Modern; 1900-2099; Exhibition catalogs; Ausstellungskatalog -- Walker Art Center -- 18.04.2020-26.07.2020 -- Minneapolis, Minn.